The parameterization method for invariant manifolds : from rigorous results to effective computations /: from rigorous results to effective computations. (2016) - Haro, A (Alex), 1969-; Canadell, Marta; Figueras, Jordi-Lluis; Luque, Alejandro; Mondelo, Josep Maria
No abstract available